A contribution to the taxonomy of Cephalaria subgen. Cephalaria (Caprifoliaceae) in eastern Turkey. Issue 1 (8th March 2018) - Ranjbar, Massoud; Ranjbar, Zahra
Abstract : Cephalaria cilodaghensis is described and illustrated as a new species from Hakkari in eastern Turkey. Cephalaria cilodaghensis is a locally endemic species, known only from the type collection and classifiable as critically endangered. Cephalaria cilodaghensis is closely related to C. hakkiarica . The diagnostic morphological characters that distinguish these species are discussed. We designated or reconfirmed the typification for four taxa of Cephalaria based on the herbarium materials at G, G‐BOIS, K, W and their related literature. Furthermore, C. speciosa is reported for the first time from northwest Iran.